2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318648
|View full text |Cite
|
Sign up to set email alerts
|

The detection and classification of the mental state elicited by humor from EEG patterns

Abstract: In this paper we investigate the use of EEG to detect the affective state of humor. The EEG of five subjects was recorded while they recalled humorous videos. Extracted frequency features were compared to a control state in which users where asked to remain in a neutral mental state. An ANOVA test performed on the two groups: neutral and humor recall found a statistically significant difference in the frequency range 28-32 Hz for a number of channels including T7 and P7. Both of which presented the greatest st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Bin Yunus, Jasmy concluded that the results obtained by independent component analysis (ICA) could provide the most accurate result for classifying emotional states in brain activity than other methods [14]. Sriharsha Ramaraju used EEG in analyzing brain activity of autism children and measure asymmetry in frontal EEG activity which is associated with motivational approach and avoidance tendencies [15]. S Koelstra created a DEAP (Database for Emotion Analysis using Physiological Signals) database and analyzes brain activity by providing different stimulus.…”
Section: Literature Surveymentioning
confidence: 99%
“…Bin Yunus, Jasmy concluded that the results obtained by independent component analysis (ICA) could provide the most accurate result for classifying emotional states in brain activity than other methods [14]. Sriharsha Ramaraju used EEG in analyzing brain activity of autism children and measure asymmetry in frontal EEG activity which is associated with motivational approach and avoidance tendencies [15]. S Koelstra created a DEAP (Database for Emotion Analysis using Physiological Signals) database and analyzes brain activity by providing different stimulus.…”
Section: Literature Surveymentioning
confidence: 99%
“…Thus, investigations using neurophysiological records such as electrophysiology (EEG) and functional magnetic resonance imaging (fMRI) should be used in order to develop affective interfaces. Using EEG data, for example, different studies using a subject-independent design combined several features and classifiers to predict the affect experienced by new participants, achieving accuracies between 70 and 95% [9][10][11][12]. Using fMRI data, accuracy varied from 60% to 80% depending on the number of voxels (from 2000 to 4000) included as predictors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigations using neurophysiological records such as electrophysiology (EEG) and functional magnetic resonance imaging (fMRI) should foster the development of affective interfaces. Using EEG data, for example, different studies using a subjectindependent design combined several features and classifiers to predict the affect experienced by new participants, achieving accuracies between 70 and 95% (Lin et al, 2010, Bozhkov and Georgieva, 2014, Georgieva et al, 2015, Ramaraju et al, 2015. Using fMRI data, accuracy varied from 60% to 80% depending on the number of voxels (from 2000 to 4000) included as predictors (Baucom et al, 2012).…”
Section: Introductionmentioning
confidence: 99%